Antioxidant activity of Piper cubeba L. berries crude extracts and its fractions - Qiang, L.S.; Rukayadi, Y.; M. Padzil, K.N.; A. Razis, A.F. (Rynnye Lyan Resources, 2022)
Traditionally, Cubeb (Piper cubeba L.) berries have been used as a spice or medicine due to their high phytochemical compounds. An earlier study has reported on the analysis of its pharmacological properties such as anti-inflammatory and antibacterial activity. Nevertheless, the antioxidant activity of P. cubeba L. berries extracts and their fractions have not been widely reported. This study aimed to determine the antioxidant activity of P. cubeba L. berries crude extracts and their fractions. Ethanol and methanol solvent was chosen to extract crude P. cubeba L. berries. Moreover, the active crude extract was fractionated using liquid-liquid partition methods into hexane, chloroform and ethyl acetate fractions. Antioxidant activity was determined by total phenolic content (TPC) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. The results showed that the TPC of ethanolic and methanolic crude extracts were 0.66±0.02 mg GAE/g and 0.59±0.01 mg GAE/g, respectively. For DPPH radical scavenging, ethanolic and methanolic P. cubeba L. berries, crude extracts showed IC50 of 546.14±3.28 µg/mL and 472.43±5.21 µg/mL, respectively. In addition, methanolic crude extracts yield hexane, chloroform and ethyl acetate fractions which have TPC values of 0.45±0.02 mg GAE/g, 0.69±0.12 mg GAE/g and 0.86±0.02 mg GAE/g, respectively. On the other hand, DPPH values IC50 give a result of 3.62±0.24 mg/mL, 197.08±0.36 µg/mL, 98.45±0.57 µg/mL to hexane, chloroform and ethyl acetate fractions, respectively. Based on the findings, P. cubeba L. crude extracts and their fractions showed high antioxidant activity. Thus, P. cubeba L. crude extracts and their fractions can be potentially developed as a natural antioxidant agent to replace synthetic antioxidants.